Sea Surface Temperature (SST) and Rainfall Trends in the Singapore Strait from 2002 to 2019 - Mubarak Mubarak; Rifardi Rifardi; Ahmad Nurhuda; Romi Fadli Syahputra; Sri Fitria Retnawaty (Faculty of Geography, Universitas Gadjah Mada, 2022)
Studying Singapore Strait waters condition as a form of maritime mitigation is necessary because it is an international shipping lane. The dominant weather changes include rainfall, wind flows, and sea surface temperature (SST). This study aims to reveal the relationship between rainfall and SST activity in the Singapore Strait for over 18 years, from 2002 to 2019. The results showed a negative correlation, where the SST decreases as rainfall increases and vice versa. In addition, the high rainfall and low SST distribution occur in the Western season (December–February). The low rainfall intensity and high (warm) SST distribution occur yearly in the transition from West to East (March–August). Also, the distribution pattern is influenced by rainfall intensity and the water mass from the South China Sea and the Malacca Strait, where the strait is a mixture of these masses. The neural network model confirmed the negative correlation. Hence a small change in SST causes rainfall if it is cooler, and less precipitation if warmer.